Impact of Preoperative Rectal Versus Intraoperative Sublingual Misoprostol on Blood Loss during Cesarean Section: A randomized clinical trial - Magdy A. Mohamed; Ahmed H. Mohammed (The Royal Thai College of Obstetricians and Gynaecologists, 2021)
Objectives: To compare blood loss between immediate preoperative rectal administration of misoprostol with intraoperative sublingual administration during elective cesarean section (CS).Materials and Methods: The patients were randomized either to receive rectal misoprostol 400 mg preoperative just after induction of anaesthesia or the same dose intraoperative sublingual. The primary outcome was estimated blood loss measurement. Secondary outcomes were change in hemoglobin concentration, need of excess oxytocin, maternal adverse effects, APGAR scores and need of admission to neonatal intensive care unit (NICU).Results: A total of 460 cases were included (230 in each group). The estimated blood loss was lower in preoperative group in comparison with intraoperative group (545 ± 232 ml versus 753 ± 256 ml). There were less reduction in hemoglobin and haematocrit value in preoperative group (0.71 ± 0.6 g/dl, 1.4 ±1.2%) when compared with intraoperative group (1.02 ± 0.8 g/dl, 1.7 ±1.3%). Also the need for oxytocin was observed in only 22.2% in preoperative group compared to 36.1% in intraoperative group. There were no differences in APGAR scores and rate of admission to NICU in both groups.Conclusion: Preoperative rectal administration of misoprostol after induction of anesthesia during elective CS was effective in decreasing blood loss with no obvious neonatal complication.